Pemanfaatan Media Sosial dalam Pengenalan Bibit Kopi Berkualitas dari UB Forest - Utari, Dwi Yanti Retno; Nintia, Sri Wahyuni; Wijayanti, Fifilia Nindi; Siwi, Dhea Alda Rahmadani Putri (PUNDIMAS: Publikasi Kegiatan Abdimas, 2024)
This Community Service (PKM) program aims to introduce quality coffee seeds from UB Forest to the coffee farming community in Malang Raya through the use of social media. Documentation and dissemination of information is carried out using the social media platform Facebook to reach a wider audience. The method of implementing this program includes preparation, implementation and evaluation stages. In the preparation stage, the PKM team conducted site surveys and initial discussions to understand field conditions and prepare relevant content. The implementation stage involves creating a Facebook account "Brawijaya University Coffee", producing digital content in the form of photos, videos and articles, as well as publishing this content via Facebook. The evaluation stage is carried out by monitoring user responses, such as the number of likes, comments and viewers on uploads, as well as conducting audience satisfaction surveys using online questionnaires. The program results show that the use of social media is effective in increasing coffee farmers' awareness and knowledge about UB Forest coffee seeds. This documentation is also important for impact analysis and evaluation of program success. It is hoped that this program can help increase the productivity and welfare of coffee farmers in Malang Raya.